Enterprise Architecture Planning for College Information Systems using the TOGAF-ADM Framework and ISO 27001 - Anwar Hilman; Dinar Rahayu; Benny Susanto (Institut Pendidikan Indonesia, 2022)
The planning for the development of Information Systems and Technology is carried out with the main goal of realizing the Vision and Mission of Higher Education. The Information System design framework used is TOGAF (The Open Group Architecture Framework) - ADM (Architecture Development Methode), in that framework consists of several steps of implementing a representative architectural design to be used in architectural design at the Toyota Indonesia Community Academy which focuses on Business, Data, Applications and Technology. For the information system security management system, TOGAF-ADM can collaborate with ISO 27001:2013, where when we plan the development of the enterprise information system architecture for universities, we must also focus on information system security in accordance with the information system security system contained in the ISO 27001 :2013. By using a combination framework between TOGAF-ADM and ISO 27001, it is very appropriate to be used as a method for planning Enterprise Architecture in Higher Education that prioritizes business, applications and technology and adopts an information security management system from ISO 27001.